Enhancing the Performance of the Standalone Rooftop SPV Module during Peak Solar Irradiance and Ambient Temperature by the Active Cooling of the Rear Surface with Spraying Water and the Front Surface with Overflowing Water - S. Sargunanathan; K. Ramanathan; S. Tharves Mohideen; S. Suresh (International Journal of Photoenergy)
The usage of the solar photovoltaic (SPV) module to meet the power demands, especially in residential and office buildings, is inevitable in forthcoming years. The objective of this study is to experimentally investigate the possibility of improving the performance of the standalone rooftop SPV module used in the residential and office buildings during peak solar irradiance and ambient temperature with active cooling of the rear surface alone by spraying water and the front surface alone by water overflowing over it and cooling of the rear and the front surfaces simultaneously. The underneath of the SPV module is attached with a tray with a length of 1580 mm, a width of 640 mm, and a depth of 100 mm. It is filled with 40-70 litres of water. Accouters are made for water overflowing from the tube over the front surface of the module and cooling of the rear surface by spraying water. The rear surface cooling, front surface cooling, and simultaneous cooling of both the surfaces reduce the average operating temperature of the module by 15.52°C (maximum 18.6°C), 24.29°C (maximum 28.7°C), and 28.52°C (maximum 34.7°C), respectively. This temperature reduction leads to the increase in the power output of the 150 W module by 10.70 W, 18.48 W, and 20.56 W and percentage increase in efficiency by 8.778%, 15.278%, and 16.895% for rear, front, and simultaneous cooling of surfaces, respectively. The net power output of the module with the front surface cooling by overflowing (0.9 litre/min) water is higher, i.e., 15.88 W/150 W, and produces installation capacity of 0.4234 watt-hour (Wh) of more energy per watt during the test period 10 AM to 2 PM in a day. The recommended cooling methods eliminate the need for freshwater and separate arrangements to dissipate the heat carried by the circulated water and reduced the power required and quantity of water circulated. They also reduced the heat loads of the room by the shadow effect and by maintaining the tray water above the roof.